Amylase and Xylanase from Edible Fungus Neurospora intermedia: Production and Characterization - Shahryari, Zohre (Molecules, 2019)
Integrated enzyme production in the biorefinery can significantly reduce the cost of the entire process. The purpose of the present study is to evaluate the production of two hydrolyzing enzymes (amylase and xylanase) by an edible fungus used in the biorefinery, Neurospora intermedia. The enzyme production was explored through submerged fermentation of synthetic media and a wheat-based waste stream (thin stillage and wheat bran). The influence of a nitrogen source on N. intermedia was investigated and a combination of NaNO(3) and yeast extract has been identified as the best nitrogen source for extracellular enzyme production. N. intermedia enzymes showed maximum activity at 65 °C and pH around 5. Under these conditions, the maximum velocity of amylase and xylanase for starch and xylan hydrolysis was found to be 3.25 U mL(−1) and 14.77 U mL(−1), respectively. Cultivation of N. intermedia in thin stillage and wheat bran medium resulted in relatively high amylase (8.86 ± 0.41 U mL(−1), 4.68 ± 0.23) and xylanase (5.48 ± 0.21, 2.58 ± 0.07 U mL(−1)) production, respectively, which makes this fungus promising for enzyme production through a wheat-based biorefinery.